2003
DOI: 10.1152/ajprenal.00377.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sustained flow perturbations on stability and compensation of tubuloglomerular feedback

Abstract: mathematical model previously formulated by us predicts that limit-cycle oscillations (LCO) in nephron flow are mediated by tubuloglomerular feedback (TGF) and that the LCO arise from a bifurcation that depends heavily on the feedback gain magnitude, ␥, and on its relationship to a theoretically determined critical value of gain, ␥ c. In this study, we used that model to show how sustained perturbations in proximal tubule flow, a common experimental maneuver, can initiate or terminate LCO by changing the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…(3), at the steady-state operating point, (F op , C op ); and (ii) the nondimensionalized slope of the steady-state TAL tubular fluid chloride concentration S(x) alongside the MD (i.e., S (L), but in dimensionless form; see Appendix A). The gain magnitudes γ A and γ B characterize the strength of the feedback response (Layton et al, 1995;Oldson et al, 2003). We write "gain magnitude" because gain would be appropriately considered a negative quantity in a negative feedback system; however, for simplicity of exposition, we will frequently use "gain" and "gain magnitude" interchangeably to mean the absolute value of the gain.…”
Section: The Characteristic Equationmentioning
confidence: 99%
“…(3), at the steady-state operating point, (F op , C op ); and (ii) the nondimensionalized slope of the steady-state TAL tubular fluid chloride concentration S(x) alongside the MD (i.e., S (L), but in dimensionless form; see Appendix A). The gain magnitudes γ A and γ B characterize the strength of the feedback response (Layton et al, 1995;Oldson et al, 2003). We write "gain magnitude" because gain would be appropriately considered a negative quantity in a negative feedback system; however, for simplicity of exposition, we will frequently use "gain" and "gain magnitude" interchangeably to mean the absolute value of the gain.…”
Section: The Characteristic Equationmentioning
confidence: 99%
“…The dependence of waveform shape on mean TAL flow may be the source of the variable degree of distortion, relative to a sine wave, seen in experimental recordings of TGF-mediated oscillations. kidney; mathematical model; renal hemodynamics; sodium chloride transport; nonlinear system IN A SERIES OF STUDIES WE have used a mathematical model of the tubuloglomerular feedback (TGF) loop to propose plausible explanations for phenomena that have been reported in experimental studies and to predict phenomena that might be found in new experimental studies (23,24,28,29,30,31,32,34,36). Our mathematical model consists of simple components that have been individually well characterized in our publications.…”
mentioning
confidence: 99%
“…The physiological significance could be that oscillations enhance renal sodium excretion (Layton et al, 2000 andOldson et al, 2003). This hypothesis is based on predictions that oscillations may enhance sodium delivery to the distal tubule and that oscillations limit the ability of the TGF system to compensate for perturbations in flow, e.g.…”
Section: Physiological Interpretationmentioning
confidence: 99%